Failed Trial of Normal Delivery in Uterus Didelphys - Rijanto Agoeng Basoeki; Rifka Florensia; Muhammad Anas (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2026)
Background: Uterus didelphys is one of the rarest anomalies from Mullery duct fusion failure. Generally, the condition is asymptomatic or can be manifest clinically as dyspareunia and/or menstrual pain, making early diagnosis challenging. Although this condition can affect fertility and risk of complications in pregnancy, in practice, the diagnosis is infrequent with the minimum awareness about the conditions.Objective: This case report aims to outline the diagnostic methods and intervention actions carried out in a patient who diagnosed uterus didelphys after failed normal delivery.Case Presentation: This paper presents a case of a 21-year-old woman who came with a complaint of tightness in the womb in two days before entering the hospital. The results of the anamnesis and physical examination show the needed of Cito LSCS surgery. During Cito LSCS, a uterus, an ovary, and a fallopian tube were found as a pair, with a fetus in the right uterus weighing 2100 g. Rehydration, antibiotic, analgetic, and laxative was given post-operative. After 3 days, patient was discharged.Conclusion: Examinations and new diagnostic methods need to be developed to identify the presence of uterus didelphys and to prevent its potential complications.